2023
DOI: 10.2967/jnumed.123.265512
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioid Release After Orgasm in Man: A Combined PET/Functional MRI Study

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The PET data revealed that pleasurable music modulated opioidergic activity in central nodes of the reward circuits such as the ventral striatum and OFC containing "hedonic hotspots" regulated by opioids (Berridge & Kringelbach, 2015). While prior [ 11 C]carfentanil PET studies on reward processing have mainly focused on biologically salient primary rewards such as feeding , sex (Jern et al, 2023), and sociability (Manninen et al, 2017), our results indicate that aesthetic rewards, such as music, that are strongly influenced by cultural learning, also modulate MOR system activity. This suggests that MORs mediate pleasure across domains, driving humans to pursue primary and non-primary rewards and make choices in the face of conflicting options (Grabenhorst & Rolls, 2011).…”
Section: Music Modulates Mor Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PET data revealed that pleasurable music modulated opioidergic activity in central nodes of the reward circuits such as the ventral striatum and OFC containing "hedonic hotspots" regulated by opioids (Berridge & Kringelbach, 2015). While prior [ 11 C]carfentanil PET studies on reward processing have mainly focused on biologically salient primary rewards such as feeding , sex (Jern et al, 2023), and sociability (Manninen et al, 2017), our results indicate that aesthetic rewards, such as music, that are strongly influenced by cultural learning, also modulate MOR system activity. This suggests that MORs mediate pleasure across domains, driving humans to pursue primary and non-primary rewards and make choices in the face of conflicting options (Grabenhorst & Rolls, 2011).…”
Section: Music Modulates Mor Activationmentioning
confidence: 99%
“…Multivariate pattern analysis of fMRI data has revealed that activity associated with subjective pleasure overlaps with regions showing mu-opioid receptor gene expression and is down-regulated by an opioid antagonist (Kragel et al, 2023). Positron emission tomography (PET) studies using the MOR-specific radioligand [ 11 C]carfentanil have revealed opioid release following biologically salient rewards such as eating and sex (Jern et al, 2023; Manninen et al, 2017), and baseline MOR availability modulates heamodynamic and behavioral responses to emotional stimuli (Manninen et al, 2017; Sun et al, 2022). Although the contribution of the MOR system musical hedonia has also been postulated (Nummenmaa et al, 2021; Tarr et al, 2014), this hypothesis remains to be tested with in vivo neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many activities that require some level of rhythmic coordination, there are few that require such tight, rhythmic coupling to achieve success, nor for which success is measured by the enjoyment of all participants (rather than in an external outcome such as locomotion in rowing). Sex also activates the same endorphin reward system as other social bonding behaviors ( Jern et al, 2023 ). Indeed, among bonobos, a close relative of humans, sexual intercourse is regularly used to maintain social bonds and mitigate conflict within a group ( Clay and Zuberbühler, 2012 ; Clay and de Waal, 2015 ).…”
Section: Evolutionary Biology Of Music and Lovementioning
confidence: 99%